Identification of mutations in the ATP7B gene in 14 Wilson disease children: Case series. Issue 16 (23rd April 2021) - Wang, Jiuxiang; Tang, Lulu; Xu, Anqi; Zhang, Shijie; Jiang, Hailin; Pei, Pei; Li, Hongmei; Lv, Tingting; Yang, Yue; Qian, Nannan; Naidu, Keegan; Yang, Wenming
Abstract: Introduction: Wilson Disease (WD) is an autosomal recessive inherited metabolic disease caused by mutations in the ATPase copper transporting beta gene ( ATP7B ). WD can cause fatal neurological and hepatic disorders if not diagnosed and treated. Objective: To analyze the disease-causing mutations of 14 Chinese WD children, 11 of whom are diagnosed with hepatic disorders, 2 with neurological degeneration and 1 with both hepatic and neurological disorders. Methods: All ATP7B coding regions were analyzed by Sanger sequencing. Single nucleotide polymorphisms (SNPs) functional impacts were assessed by combining the results of four bioinformatics tools (Poly-phen-2, SIFT, PANTHER-PSEP and PhD-SNPs) in an index that reflects the combined probability (cPdel ) of an amino acid change to be deleterious to the protein function. Results: Two novel variants involved in WD development, c.1448_1455del (p.Arg483SerfsX19) and c.4144G>T (p.Glu1382Stop), and 11 previously reported mutations were detected. Both new variants result in shortened and dysfunctional ATP7B proteins. cPdel score suggests that SNPs may be deleterious to the ATP7B functionality. Conclusions: This study enriches the library of the ATP7B mutations that lead to WD and can be used as a basis for genetic counseling, for WD prevention and clinical and prenatal diagnosis. Those SNPs that are believed to be harmless to ATP7B protein may be involved in the pathogenesis of WD. Abstract : Supplemental Digital Content is available in the text